2014
DOI: 10.3109/01612840.2014.901450
|View full text |Cite
|
Sign up to set email alerts
|

Women's Functioning Following an Intervention for Partner Violence: New Knowledge for Clinical Practice from a 7-Year Study

Abstract: Intimate partner violence affects one in three women worldwide, with women who experience violence almost twice as likely to experience poor mental health, especially depression, compared with women who are not abused. To learn the impact of interventions of safe shelter and justice services on improved mental health and behavior functioning, 300 abused women are interviewed every 4 months in a 7-year prospective study. For this paper, abuse, mental health and resiliency status of these women, 1 year after acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…However, these initial impacts at T2 may not have persisted due to lack of ongoing structural support outside of the nurse delivered intervention, as this intervention did not address social norms or community context, or seek to improve other support services for women experiencing violence. A 7-year, US-based prospective study of women who sought social services for IPV experiences yielded similar short- and long-term findings regarding mental health [31]. Other health sector-based RCTs in non-LMIC settings have shown mixed findings regarding improvements in mental health, including quality of life [5, 10, 32].…”
Section: Discussionmentioning
confidence: 96%
“…However, these initial impacts at T2 may not have persisted due to lack of ongoing structural support outside of the nurse delivered intervention, as this intervention did not address social norms or community context, or seek to improve other support services for women experiencing violence. A 7-year, US-based prospective study of women who sought social services for IPV experiences yielded similar short- and long-term findings regarding mental health [31]. Other health sector-based RCTs in non-LMIC settings have shown mixed findings regarding improvements in mental health, including quality of life [5, 10, 32].…”
Section: Discussionmentioning
confidence: 96%
“…In their sample, PTSD was associated with family of origin sexual abuse and higher current levels of financial difficulties. Koci et al 8 reported that 12 months after seeking a restraining order from a District Attorney's office or safe shelter in a woman's shelter, 39.2% of women had clinical level PTSD symptom scores.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, one in 15 children may witness partner violence every year (Hamby, Finkelhor, Turner, & Ormrod, 2011). In samples of women who experienced partner violence and sought assistance from the justice department or from a shelter, from 39% (Koci et al, 2014) to 47% (Johnson & Zlotnick, 2012) experienced chronic posttraumatic stress disorder (PTSD). When mothers experience partner violence and have PTSD, their children are at greater risk for behavior problems than children whose mothers experience partner violence but do not have PTSD (Symes, McFarlane, Fredland, Maddoux, & Zhou, 2016; van Ee, Kleber, & Jongmans, 2016).…”
mentioning
confidence: 99%